2017
DOI: 10.1002/chem.201703440
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic A2V Mutant Exhibits Distinct Aggregation Kinetics, Metal Site Structure, and Metal Exchange of the Cu2+–Aβ Complex

Abstract: A prominent current hypothesis is that impaired metal ion homeostasis may contribute to Alzheimer's disease (AD). We elucidate the interaction of Cu with wild-type (WT) Aβ and the genetic variants A2T and A2V which display increasing pathogenicity as A2T Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 44 publications
6
26
0
Order By: Relevance
“…The experiments performed on the apopeptides yielded results very similar to those presented in the literature for Aβ 1–40 and Aβ 4–40 [33, 35, 62, 84] . The ThT fluorescence intensity spectra of the Aβ 1–40 aggregation follows a steep and asymmetrical S‐shaped curve with a growth phase that slows with time.…”
Section: Discussionsupporting
confidence: 79%
“…The experiments performed on the apopeptides yielded results very similar to those presented in the literature for Aβ 1–40 and Aβ 4–40 [33, 35, 62, 84] . The ThT fluorescence intensity spectra of the Aβ 1–40 aggregation follows a steep and asymmetrical S‐shaped curve with a growth phase that slows with time.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, in the study of Somavarapu et al [53], reviewed in section 2.1, Cu(II) shows a more pronounced propensity to extend the lag phase, especially for the pathogenic A2V. A fast, low intensity ThT response has been observed at the first hours of the in vitro aggregation experiment.…”
Section: Impact Of Cu and Zn On The Aggregation Of Aβ αSyn And Hiappmentioning
confidence: 98%
“…The mutation of Ala2 is an interesting one: A2V is highly pathogenic [50], while A2T has shown a protective effect [51]. EPR studies show a similar Cu(II) coordination for the WT and the A2 mutants, but changes on the pK a values of the transition between component I and component II, which could be key for a pathological role of Cu-Aβ binding [52,53]. In fact, with a pK a for A2V of 8.4 (7.4 for A2T, 7.8 for WT), component I is stabilized at physiological pH.…”
Section: Coordination Of Cu and Zn To Amyloid-β α-Synuclein And Amylmentioning
confidence: 99%
See 1 more Smart Citation
“…Super-stoichiometric concentrations of Cu(II) and Zn(II) easily induce rapid formation of amorphous aggregates without amyloid structures, where the metal ion might bind to a second binding site and possibly bridge between Aβ peptides (9,31,32). In contrast, substoichiometric Cu(II) (33,34) or Zn(II) concentrations retard the overall fibrillization process, and our previous study on Zn(II) revealed the specific reduction of the fibril-end elongation (14). Besides Cu(II) and Zn(II), several other transition metal ions bind to the Aβ peptide, competing for similar ligands with slightly different coordination modes (13,(19)(20)(21).…”
Section: ________________________________________mentioning
confidence: 99%